Inflamed Mesenteric Lymphangioma Mimicking an Infiltrative Abdominal Tumor in a 5-Year-Old Girl - Malo, Eltona; Cinari, Suela; Heta, Saimir (International Journal of Innovative Research in Medical Science, 2025)
<!--StartFragment--> Abdominal lymphangiomas are rare benign malformations of the lymphatic system that can mimic more aggressive pathologies when complicated by infection or hemorrhage. We present the case of a 5-year-old female with acute abdominal pain, low-grade fever, and vomiting, whose imaging findings raised concern for an infiltrative mesenchymal tumor. The final diagnosis following surgical resection and histopathologic evaluation was infected mesenteric lymphangioma. This case underscores the diagnostic challenges of lymphangiomas and the importance of combining clinical, imaging, and histological data in pediatric abdominal masses. <!--EndFragment-->